Improving Students’ Procedural Text Writing Skills Through Project-Based Learning - Sulkiman Sulkiman; Yessi Fitriani; Puspa Indah Utami (Journal of Social Work and Science Education, 2026)
This study aims to improve the procedural text writing ability of fifth-grade students at SDN 3 Banyuasin II through the implementation of the Project Based Learning (PjBL) model. Classroom Action Research (CAR) was conducted over multiple cycles, each comprising planning, action implementation, observation, and reflection. Subjects were 25 fifth-grade students in the 2025/2026 academic year. Data were collected through observation and written tests, using student activity observation sheets and a procedural text writing rubric assessing title, objectives, tools/materials, and steps. Analysis employed descriptive quantitative and qualitative techniques. The PjBL model proved highly effective in improving writing abilities. Student learning completion increased dramatically from 16% at initial condition to 88% at the final cycle, surpassing the established Learning Objective Achievement Criteria (KKTP). This significant improvement demonstrates that project-based learning enhances both student engagement and the quality of procedural text composition. The research provides empirical validation of PjBL’s effectiveness specifically for procedural text writing at the elementary level, a genre requiring sequential, practical skill demonstration. Teachers can adopt the PjBL model as a proven strategy for developing structured writing competencies, with the observed assessment rubric serving as a practical evaluation tool. The study contributes classroom-based evidence supporting project-based approaches for foundational literacy development, demonstrating how active, collaborative learning can transform writing instruction outcomes.